2013
DOI: 10.1111/nin.12028
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing structural violence in the context of mental health nursing

Abstract: This article explores how the intersections of gendered, racialized and neoliberal dynamics reproduce social inequality and shape the violence that nurses face. Grounded in the interviews and focus groups conducted with a purposeful sample of 17 registered nurses (RNs) and registered practical nurses (RPNs) currently working in Ontario's mental health sector, our analysis underscores the need to move beyond reductionist notions of violence as simply individual physical or psychological events. While acknowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 34 publications
(37 reference statements)
0
30
0
Order By: Relevance
“…28 Feminist political economy concerns itself with the conditions, pressures, and structures that shape environments and practices and the relevance of gender in that context. 29 Applying an intersectional lens that foregrounds race and gender shaped a grounded theory pointing out notions of agency for racialized immigrant women, a fresh approach to studies that focus on immigrant women's mental health. 30 There is transformative potential in showing how counterdiscourses challenge taken-for-granted knowledge and practices at the structural level and illuminate actions consistent with social justice.…”
Section: Critical Feminist Methodologiesmentioning
confidence: 99%
“…28 Feminist political economy concerns itself with the conditions, pressures, and structures that shape environments and practices and the relevance of gender in that context. 29 Applying an intersectional lens that foregrounds race and gender shaped a grounded theory pointing out notions of agency for racialized immigrant women, a fresh approach to studies that focus on immigrant women's mental health. 30 There is transformative potential in showing how counterdiscourses challenge taken-for-granted knowledge and practices at the structural level and illuminate actions consistent with social justice.…”
Section: Critical Feminist Methodologiesmentioning
confidence: 99%
“…Numerous structurally situated factors influence nurses' work lives have been highlighted in the broader nursing literature as being significant contributors to their risk environments (Anderson et al., McGibbon, Peter, & Gallop, 2010). These include: hierarchical and gendered power inequities arising from the historical legacy of patriarchy and the privileging of the medical profession (Choiniere, MacDonnell, Campbell, & Smele, ; Dossey, ; McGibbon et al., ); crushing workloads and poor working conditions resulting from oppressive corporate management strategies (Rankin, ) that unduly predispose them to physical injuries (Shields & Wilkins, ); devaluation of their caring work and emotional labor (Choiniere et al., ; McGibbon et al., ; Rankin, ); high levels of emotional, physical, and horizontal violence in their workplaces (Hesketh et al., ; Longo & Sherman, ); and being subject to secondary traumatic stress (Dominiquez‐Gomez & Rutledge, ) and moral distress (Pauly, Storch, & Varcoe, ).…”
Section: Contributory Factors Of Access Stress and Attitudementioning
confidence: 99%
“…Choiniere et al . () demonstrated that increased workload, a changing work environment, and lack of resources increased emotional stress, and this emotional stress influenced nursing staff members’ experiences with violence. Blando et al .…”
Section: Discussionmentioning
confidence: 99%
“…Violence against nurses has increased in healthcare settings (Choiniere et al . ; Gillespie et al . ) and particularly in psychiatric nursing (Maguire & Ryan ; Nolan et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation